A Comparison Of Emergence Agitation Between Succinylcholine And Rocuronium (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Agitation immediately after EA operation is one of the common problems during recovery, especially in children. In general, agitation is defined as a set of physical symptoms or emotional distress that includes the following symptoms alone or together: crying, restlessness, clutching, demonstrations, verbal kicking, and purposeful or purposeless behaviors that may have a logical connection.Method:In this study, 60 patients in the age range of 20 to 50 years who were in ASA I and II categories were subjected to tracheal intubation in two groups by rapid sequence induction method. The first group received 3 μg/kg of fentanyl and 0.5 mg/kg of lidocaine for premedication and were given induction with 1 mg/kg of succinylcholine and 5 mg/kg of nesdonal. The second group received 3 μg/kg of fentanyl and 0.5 mg/kg of lidocaine for premedication and were given induction with 0.6 mg/kg of rocuronium and 5 mg/kg of nesdonal. After surgery, the incidence, intensity and duration of agitation when the patient woke up in both groups was recorded by a physician based on Riker's criteria. Also, the occurrence of myalgia and its persistence from one to 24 hours after the operation were assessed.Results: According to the results of this clinical trial, succinylcholine and rocuronium were not significantly different from each other in terms of the occurrence of agitation, its intensity and duration, but based on the results of the odds ratio, the probability that in patients who took rocuronium they found that agitation is 0.6 times less than the patients who received succinylcholine. Logistic analysis of the data also showed that in patients who received succinylcholine, the probability of agitation being more severe is 2.47 times higher than in patients who received rocuronium. The duration of agitation in patients receiving succinylcholine was also higher than in patients receiving rocuronium. In terms of the incidence and severity of myalgia, there was no significant difference in the people who received rocuronium or succinylcholine, however, a total of 50% of the patients showed agitation symptoms, showed myalgia, of which 16.6% were related to the people who received rocuronium and 33.3% were related to patients who received succinylcholine. The results of the myalgia odds ratio also showed that the probability of myalgia symptoms being observed in patients who received rocuronium is 0.5 times lower than in patients who received succinylcholine.